Non-native golden dorado, Salminus brasiliensis (Characiformes: Bryconidae): A threat to biodiversity in the Preguiças River, Northeastern Brazil - Jamerson Aguiar-Santos; Mairton Batista Meneses (Zoologia (Curitiba))
ABSTRACT The emergence of non-native species as a threat to local biodiversity is a pressing concern that warrants immediate attention. Our study reports the first record of the non-native fish golden dorado, Salminus brasiliensis, for the Preguiças River Basin, Maranhão State, Northeastern Brazil, near the Parque Nacional dos Lençóis Maranhenses (PNLM). This discovery occurred when a single adult, measuring 77 cm in total length, was captured by artisanal fishers using gillnets in January 2024. This finding underscores the importance of ongoing monitoring efforts focused on the ichthyofauna of the Preguiças River Basin: the tributaries of the lower portion of the basin are located within and at the border of the PNLM area. Such monitoring initiatives are essential for comprehending the distribution range of S. brasiliensis and evaluating its potential impacts on local native freshwater species.